La Scuola dopo la DaD. Riflessioni intorno alle sfide del digitale in educazione - Maria Ranieri (Firenze University Press, 2021)
The article presents a reflection on the digital challenges for education while considering the complexity characterizing the current socio-cultural scenarios, severely marked by the health emergency due to the spread of Coronavirus. Moving from an examination of the trends that emerged during the lockdown with respect to the use of technologies to support teaching and learning processes, a multidimensional analysis of the factors to be taken into account for quality digital teaching is proposed. In doing so, it attempts to overcome the unfruitful  dichotomous visions and depicting a future for schools after distance learning where the educational technologies topic is associated to the themes of quality training, learning design, formative evaluation and digital equity.